Self-employment duration in urban and rural locations - Hannu Tervo; Mika Haapanen (European Regional Science Association (ERSA), 2005)
Previous research has shown that local environment is important for self-employment. Self-employment dynamics varies between areas characterized by different labour market conditions, entrepreneurial tradition and other structural factors. Alternation between different labour market states (self-employment, paid-employment, non-employment) is also likely to increase if employment opportunities remain low in local labour market markets. This paper analyses the factors influencing the duration of self-employment spells in Finland with a large registered-based data set from the period of 1987-2002. It is evident that rates of exit out of self-employment and the length of self-employment spells depend upon personal characteristics and cyclical trends in the economy. The main aim is to analyse the role of region-specific factors as compared with individual specific and other factors on the duration of self-employment spells. Self-employment duration is modelled by using discrete survival analysis. First, descriptive analysis is done. Second, simple Cox proportional hazard models are estimated. Third, more complex hazard models e.g. with competing risks are used.
Keywords: 330